Uma Arquitetura para Experimentação de Novos Serviços na Plataforma Orientada a Aplicações da TV 3.0 - Santos, Joel dos; Sodré, Rodrigo da Mota; Ribeiro Junior, Luís Claudio; Amorim, Glauco; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
TV 3.0 brings several new functionalities to the Brazilian DTV system. Among these functionalities, it is possible to highlight the Application-Oriented Platform (AoP), execution of Ginga applications, viewer profile creation, and connection with smart devices using a local network. Given the wide spectrum of functionalities present in TV 3.0, this work proposes an architecture for experimenting with TV 3.0 AoP services. This architecture is designed to be extensible such that developers can easily create/extend its functionalities. To indicate its usefulness and versatility, this work presents two use cases implemented over this proposed architecture.